Na cozinha do Masterchef Brasil 2020: uma análise dos memes dos fãs da competição culinária através da #masterchefbr - Romano, Kelly Amorim (Universidade do Vale do Rio dos Sinos, 2021)
This research has as its main focus to analyze the memes published by fans of the Masterchef Brazil culinary competition about the new format presented in the 7th season through #MasterchefBr on the social network twitter. As a way to interpret the way the fan reacted to the new model adopted by the reality show, we outlined two specific objectives in order to investigate the effect of this change. The specific objectives are to seek to understand the impact of replacing the old format with the new one due to the Coronavirus pandemic; and identify the message and meaning of the meme posts by the show's fans with #MasterchefBr on twitter. To carry out the analysis, it was necessary to enter, at first, the theoretical concepts considered fundamental for understanding the research theme, such as memes in Brazil, participatory culture and fans. In a second moment, we applied the documentary research through content analysis as a means of separating, categorizing and analyzing the meaning of the memes tweeted with the hashtag by fans of the program about the 7th season of the reality show, as well as observing the repercussion and reception of the same about the new format. We conclude that, as a result of the negative movement around #MasterchefBr about the model for the new season, the reality show delivered one last episode in an attempt to offset the disappointment of fans of the culinary competition.
Keywords: #masterchefbr; Cultura participativa e os fãs; Twitter; Reality show; Participatory culture and fans